2009
DOI: 10.1063/1.3186785
|View full text |Cite
|
Sign up to set email alerts
|

Observation of space-separated multiexciton generation in photocurrent of Au/por-Si/p-Si structure

Abstract: Dominating radiative recombination in a nanoporous silicon layer with a metal-rich Au ( 1 − α ) -Si O 2 ( α ) cermet waveguide Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Over the past two decades, porous Si films have attracted considerable interest in fundamental research and potential device applications, e.g., gas sensors to detect toxic and explosive gases [1][2][3], high capacity anodes for lithium-ion (Li + ) batteries [4,5], multiexciton solar cells [6,7], biosensors [8], drug delivery devices [9,10], and light emitting devices [11,12]. To date, a number of interesting fundamental properties have been reported; however, applications are not yet sufficiently advanced.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, porous Si films have attracted considerable interest in fundamental research and potential device applications, e.g., gas sensors to detect toxic and explosive gases [1][2][3], high capacity anodes for lithium-ion (Li + ) batteries [4,5], multiexciton solar cells [6,7], biosensors [8], drug delivery devices [9,10], and light emitting devices [11,12]. To date, a number of interesting fundamental properties have been reported; however, applications are not yet sufficiently advanced.…”
Section: Introductionmentioning
confidence: 99%
“…With U b varied within the range −0.02÷−0.8 V (reverse bias), the DLTS spectra measured in the dark exhibited two broad DLTS peaks: high-temperature peak E1, the amplitude of which substantially exceeds that of the lowtemperature peak E3 (figure 6, curve 1). The rather large halfwidths of the peaks may be caused both by the dispersion of Si nanoparticles in the layer [3][4][5][6], and by the statistical distribution of states in amorphous a-Si. In [17], the model of size-dependent luminescence from a-Si:H is analyzed and it is shown that a blue shift of the luminescence energy and a general increase in the quantum efficiency of luminescence are predicted as the structure size decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Using the achievements of nanotechnology makes it possible to significantly improve the characteristics of silicon SCs. In several studies silicon nanoparticles were used as an additional intermediate layer in a SC to raise the absorption in the short-wavelength part of the spectrum [2] and as a layer providing better utilization of the UV part of the solar spectrum via impact ionization [3]. However, the absorption of light in quasi-zero-dimensional is substantially lower than that in devices based on thin film semiconductors because of the low density of the obtained layers.…”
Section: Introductionmentioning
confidence: 99%
“…В нанокристаллах на основе пористого кремния, выращенных на подложке монокристаллического кремния, Au/por Si/p-Si (E g = 1.8 эВ) также наблюдалась раздельная мультиэкситонная генерация двух " горячих" электронно-дырочных пар и двукратное возрастание интенсивности фотолюминесценции в спектральном диапазоне 1.6−2.4 эВ при освещении высокоэнергетическими фотонами с энергией > 3.5 эВ, обусловленное ударной ионизацией [64].…”
Section: особенности процессов ударной ионизации и умножения носителеunclassified